2018
DOI: 10.3390/min8050201
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Pigments in Archaeology: Their Analysis and the Range of Available Materials

Abstract: Naturally occurring minerals or their synthetic analogues have been important as pigments used in artistic and cosmetic contexts in global antiquity. The analysis and identification of mineral pigments, though routine to the petrologist or mineralogist, also requires specialist knowledge of the archaeological contexts and available technologies and trade. This paper attempts to present an analytical approach to the study of mineral pigments in archaeology and also introduces the range of mineral pigments encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 163 publications
3
99
0
3
Order By: Relevance
“…The MA-XRF maps make possible to identify the materials mainly used for the decorations of the walls of the Villa della Piscina: although it was not possible to reveal quantitative data, the maps (Figure 3) show that the fragments shared a pictorial palette that includes common materials used by Roman artists. [11][12][13] Among these, Egyptian blue and iron-oxide compounds are the main pigments used in these samples, as summarized in Table 1. IBA measurements were carried out in point-like mode, selecting the spots to be analysed according to the elemental maps obtained by the scanning-mode MA-XRF measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MA-XRF maps make possible to identify the materials mainly used for the decorations of the walls of the Villa della Piscina: although it was not possible to reveal quantitative data, the maps (Figure 3) show that the fragments shared a pictorial palette that includes common materials used by Roman artists. [11][12][13] Among these, Egyptian blue and iron-oxide compounds are the main pigments used in these samples, as summarized in Table 1. IBA measurements were carried out in point-like mode, selecting the spots to be analysed according to the elemental maps obtained by the scanning-mode MA-XRF measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The use of green earth in Roman F I G U R E 5 Correlation between Cu and Si concentrations in the analysed fragments. The differently coloured data point corresponds to the different hues of the pigments (see Table 2) [Colour figure can be viewed at wileyonlinelibrary.com] 7.32 (9) 0.062 (5) 0.0274 161.175 154.20 40.187 7Sample 40 White 8.64 (15) 0.169 (15) 14.08 (19) 0.064 (4) 0.0267 151.382 91.490 (8) 0.0130 138.3 (4) Green/blue 11.01 161.029 (28) 10.74 (12) 0.087 (6) 0.0389 226.50 (10) 0.0244 (20) 0.0132 (11) 0.086 (6) Red 5.30 (11) 0.272 (17) 15.62 (21) 0.117 (6) 0.0613 245.406 210.0087 (9) 0.0163 (12) 0.866 (12) 0.187 7Brown 2.32 (9) 0.175 (21) 19.9 (3) 0.093 (8) 9.89 (14) 0.0087 (12) 0.0218 (17) 0.144 (9) Green 3.83 (10) 0.112 (16) 17.44 (27) 0.044 (5) 0.0292 (19) 5.12 70.0149 …”
Section: Resultsmentioning
confidence: 99%
“…Classical sources (Pliny, Vitruvius, Theophrastus) reported that the best red ochre was generally imported from Anatolia (i.e. sinopia) but such pigment was also obtained by grinding, sieving and burning a natural red earth containing iron oxides/ hydroxides and other silicates for achieving the intense red colour [46]. In the past such red earths were generally imported [32] but it should be noted that possible exploitation sources also outcropped near Paestum in the Apennine sequences of the Salerno province [26]; thus, their exploitation in the past for the production of this red pigment cannot be excluded.…”
Section: Plos Onementioning
confidence: 99%
“…The occurrence of accessory monazite and clinoatacamite, malachite, barite, and mixite, associated with azurite in the addressed paint layers were used to infer a plausible pigment provenance [29,30]. The associated atacamite and clinoatacamite can be interpreted as intentional additions to the mixture, accessory minerals proxies of the ore deposit, or weathering product [31]. In fact, the chlorides, atacamite and clinoatacamite, already used as pigments by Egyptians and easily synthetized by alchemic processes, originate naturally in the azurite deposits and, after pigment application, as weathering products in the presence of Cl compounds.…”
Section: Bluementioning
confidence: 99%
“…Green earths originate in glauconite and/or celadonite [38,39], associated with different geological environments. In fact, celadonite occurs as an alteration of basaltic rocks, whereas glauconite is derived from alteration of marine clays and sandstones [31,40,41]. Based on historical art supply data from the coeval technical essays, mineral identification helped in inferring provenance for the used green earth pigments.…”
Section: Greenmentioning
confidence: 99%